Project appraisal: a refection - Moutinho, Nuno (2013)
We present project evaluation approaches that should be used as a basis for decision. We try to fi nd what aspects must be taken into account in project analysis, acknowledging the need to consider intangible aspects that are impossible to measure and that lead to subjective analysis to project evaluators. We also wish to understand if fi rms have adequate tools and methods that incorporate and quantify all non nancial aspects. We have identi ed several other aspects that infl uence projects' evaluation and decision-making. This is not a mere fi nancial activity, but involves a diversity of behavioural and organizational factors, and business perception, which should be adequately adjusted to invest with success.